Income generation and empowerment pathways for rural women of Jagusi Parish, Uganda: A double-sided sword. Issue 1 (2021) - Haley, Chelsea; Marsh, Robin
Abstract: This paper contributes to the growing literature on women's economic empowerment by exploring the relationship between women's engagement in income-generating activities (IGAs) and their capacity to realize self-defined goals, centered on well-being and decision-making. Mixed methods data were analyzed to understand local conceptualizations of an 'empowered' woman in Jagusi Parish, Uganda. Women participated in a survey and an innovative Card Sorting Game (CSG), choosing scenario cards that they 'experienced' or 'aspired to experience' in the future, then ranking and describing their choices. The scenarios were designed by local health and development practitioners together with the research team and pre-tested with village women. Experiences with these scenarios were then compared for women engaged and not engaged in income-generating activities to see how IGAs may create, or widen, empowerment pathways for local women. While structural barriers of poverty and gender discrimination remain major challenges in Jagusi, this study provides evidence that in some important ways, such as educating children and sharing decisions on family budgets, engagement in IGAs has advanced women's empowerment in line with what Jagusi women value most. The evidence also shows that women's engagement in IGAs is important in poverty management but for most households has not proven to be transformational in lifting families out of poverty. Highlights: An innovative visual Card Sorting Game (CSG) mitigates use of Westernized and often inaccurate notions of local empowerment. Jagusi women see empowerment as joint decision-making and mutual dependence, not necessarily autonomy. Jagusi women engaged in income generation experience more self-defined empowerment scenarios revealed through CSG selections. Earning money independently opens pathways for many women to question norms and expand future horizons. Results lean toward integrated and locally-designed interventions to support women's economic empowerment.